Tribological Performances of Thermosetting Polyimide Matched with Steel and Ceramic. Issue 1 (2nd January 2016) - Wang, Yanming; Cai, Peng; Chen, Shoubing; Tao, Liming; Wang, Tingmei; Wang, Qihua
ABSTRACT: The tribological properties of thermosetting polyimide (TPI) mated with Si3 N4, Al2 O3, and GCR15 balls are investigated from room temperature to 300°C. TPI mated with ceramic balls shows a lower coefficient of friction (COF) and wear rate (WR) at room temperature due to the lack of a transfer film on TPI–ceramic balls, which is demonstrated by energy-dispersive spectroscopy (EDS) and different wear mechanisms. A conclusion is drawn that a transfer film cannot form on ceramic balls due to the low chemical activities of ceramic materials, especially under higher load conditions. Under high temperatures, COFs of TPI–ceramic balls present a diverse trend compared to TPI–GCR15. Moreover, transfer films on ceramic balls begin to form as the temperature increases, which is easily determined by EDS of the tribological marks on ceramic balls. The differences presented above can mainly be ascribed to the diversities of different properties of mated balls.